Fiscal equalisation: Principles and an application to the European Union - Bernd Hayo; Matthias Wrede (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2001)
The paper derives a normative model for partial fiscal equalisation based on a number of axioms and makes special allowance for the existence of a specific fiscal need in the jurisdictions. A simple version of this idealised equalisation scheme relates net contributions to the equalisation funds to deviations of a jurisdiction's gross income from average gross income and a jurisdiction's specific needs from average specific needs. The theoretical model is then empirically tested for the case of the European Union using data from 1986-97. It is found that most restrictions of the model appear to hold, in particular, relatively richer countries contribute more and those with greater fiscal needs, approximated by the importance of the agricultural sector, pay less. However, in the EU, an adjustment of net payments to changes in the actual importance of the specific fiscal need for a country is lacking.
Keywords: H77; H87; 330; Fiscal Equalisation; European Union; Finanzausgleich; Theorie; EU-Staaten